Os instrumentos legais sobre drogas e a produção de sentidos sobre o usuário : entre o proibicionismo, a (des)criminalização e a redução de danos - Dantas, Suene de Souza (2016)
The goal of this Dissertation is to analyze the influence of legal instruments concerning drugs on the way that the drug users perceive themselves and are socially perceived. Thus, an empiric research was developed at Psychosocial Care Centers for alcohol and other drugs (CAPS ad), together with the users and the professionals from this service. The ethnographic fieldwork (GEERTZ, 1973) lasted six months, including the direct observation and semi-structured interviews, that were analyzed in reference to the theoretical methodical approach of “discursive practices” (SPINK, 2004). One focus point was on how the interlocutors are influenced by the legal discourses, for example about prohibitionism, harm reduction, the current law on drugs (N°11.343 / 2006) and the public policy on drugs, investigating in which way these are producing meanings. Further investigating the elements involved in the construction of the user category and in the way what the health professionals think about the matter/issue of drugs, how they perceive the users and conduct their works practices. Finally, how these conceptions are affected by the legal instrument and manifested by the professionals and therefore affect how the users perceive themselves, conceptualize the substances, conceive the drugs law and influence the relationship that users established with the healthy services. In the period of the research, I notice that the criminalization of drug use intervened negatively in the way that the users are socially perceived, which is in fact affecting their health care. A possible change can be seen in the harm reduction programs, however, the elaboration of progress strategies become limited by the prevalence of the prohibitionist based and still drug criminalizing Brazilian legislation. Thus, the discussion about drug's decriminalization or drug's regulation is a present and ongoing topic. Thereby, in the first chapter, I describe the negotiation process, the integration, adaptation and the process itself of the research accomplished at CAPS ad. In the second chapter, I contextualize the user term, seeking to comprehend it from the legal instrument about drugs and the space where this norms have regulatory function, like in this case, the CAPS ad. In the third chapter, I discuss how the legal framework is transmitted through the daily practice, in the contact and dialog between the interlocutors, with the intention to understand how the subject is constituted in this discursive web and how it refuses or identifies itself with the dominant discourses.